Safety of corticosteroids in young children with acute respiratory conditions: a systematic review and meta-analysis. Issue 8 (1st August 2019) - Fernandes, Ricardo M; Wingert, Aireen; Vandermeer, Ben; Featherstone, Robin; Ali, Samina; Plint, Amy C; Stang, Antonia S; Rowe, Brian H; Johnson, David W; Allain, Dominic; Klassen, Terry P; Hartling, Lisa
Abstract : Objective: Adverse events (AEs) associated with short-term corticosteroid use for respiratory conditions in young children. Design: Systematic review of primary studies. Data sources: Medline, Cochrane CENTRAL, Embase and regulatory agencies were searched September 2014; search was updated in 2017. Eligibility criteria: Children <6 years with acute respiratory condition, given inhaled (high-dose) or systemic corticosteroids up to 14 days. Data extraction and synthesis: One reviewer extracted with another reviewer verifying data. Study selection and methodological quality (McHarm scale) involved duplicate independent reviews. We extracted AEs reported by study authors and used a categorisation model by organ systems. Meta-analyses used Peto ORs (pORs) and DerSimonian Laird inverse variance method utilising Mantel-Haenszel Q statistic, with 95% CI. Subgroup analyses were conducted for respiratory condition and dose. Results: Eighty-five studies (11 505 children) were included; 68 were randomised trials. Methodological quality was poor overall due to lack of assessment and inadequate reporting of AEs. Meta-analysis (six studies; n=1373) found fewer cases of vomiting comparing oral dexamethasone with prednisone (pOR 0.29, 95% CI 0.17 to 0.48; I 2 =0%). The mean difference in change-from-baseline height after one year between inhaled corticosteroid and placebo was 0.10 cm (two studies, n=268; 95% CI −0.47 to 0.67). Results from five studies with heterogeneous interventions, comparators and measurements were not pooled; one study found a smaller mean change in height z-score with recurrent high-dose inhaled fluticasone over one year. No significant differences were found comparing systemic or inhaled corticosteroid with placebo, or between corticosteroids, for other AEs; CIs around estimates were often wide, due to small samples and few events. Conclusions: Evidence suggests that short-term high-dose inhaled or systemic corticosteroids use is not associated with an increase in AEs across organ systems. Uncertainties remain, particularly for recurrent use and growth outcomes, due to low study quality, poor reporting and imprecision.